miR-186-ANXA9 signaling inhibits tumorigenesis in breast cancer - Zhongrui Wang; Zhongrui Wang; Xiqian Zhou; Xiaochong Deng; Danrong Ye; Diya Liu; Baian Zhou; Wenfang Zheng; Xuehui Wang; Yuying Wang; Oyungerel Borkhuu; Lin Fang; et al. (Frontiers in Oncology, 2023)
Breast cancer (BC) ranks as the highest incidence among cancer types in women all over the world. MicroRNAs (miRNAs) are a class of short endogenous non-coding RNA in cells mostly functioning to silence the target mRNAs. In the current study, a miRNA screening analysis identified miR-186-5p to be downregulated in human breast cancer tumors. Functional studies in vitro demonstrated that overexpression of miR-186-5p inhibited cellular proliferation and induced cell apoptosis in multiple breast cancer cell lines including MDA-MB-231, MCF-7, and BT549 cells. Transplantation of the miR-186-5p-overexpressing MDA-MB-231 cells into nude mice significantly inhibited mammary tumor growth in vivo. Sequence blast analysis predicted annexin A9 (ANXA9) as a target gene of miR-186-5p, which was validated by luciferase reporter assay, QRT-PCR analysis, and western blot. Additional gene expression analysis of clinical tumor samples indicated a negative correlation between miR-186-5p and ANXA9 in human breast cancer. Knockdown of ANXA9 mimicked the phenotype of miR-186-5p overexpression. Reintroduction of ANXA9 back rescued the miR-186-5p-induced cell apoptosis. In addition, miR-186-5p decreased the expression of Bcl-2 and increased the expression of p53, suggesting a mechanism regulating miR-186-5p-induced cellular apoptosis. In summary, our study is the first to demonstrate miR-186-5p-ANXA9 signaling in suppressing human breast cancer. It provided a potential therapeutic target in breast cancer.